Carbon materials for high-voltage supercapacitors. (April 2019) - Liu, Ching-Fang; Liu, Yu-Chien; Yi, Tien-Yu; Hu, Chi-Chang
Abstract: Researches on electrochemical energy storage devices with a high energy density have attracted the tremendous attention in recent years due to the ever-growing energy demands and rapid development of electric vehicles. Carbon-based materials are widely employed as the electrode materials in supercapacitors (SCs) which are promising devices for highly efficient energy and power managements. However, such devices suffer from the moderate energy densities in common organic liquid electrolytes compared to secondary batteries, significantly limiting their future applications. To circumvent this issue, enlarging the working cell voltage of SCs is a more effective strategy for increasing the energy density in comparison with enhancing the specific capacitance. This critical review points out the potential strategies for enlarging the working cell voltage and surveying recent achievements of high cell voltage SCs obtained through the modification and development of hybrid systems. Various factors influencing the operating cell voltage of carbon-based materials are discussed from the intrinsic property viewpoints of carbon. Consequently, we make an in-depth summary on various promising approaches of significant breakthroughs in recent years and provide the strategies to choose suitable carbon materials or modification methods for approaching the high-voltage SCs. Graphical abstract: The AC-based EDLCs employing common organic liquid electrolytes suffer from the moderate energy density because of the relatively low cell voltages of 2.5–2.7 V. Enlarging the working cell voltage of SCs, achieved by different combinations among electrode materials and electrolytes, is a more effective strategy for increasing the energy density in comparison with enhancing the specific capacitance of electrode materials. In addition, there are four general strategies: change in electrolytes, control of surface functional groups on carbons, modification of carbon surface, and asymmetric/hybrid designs, to achieve the high-voltge SC purpose.Image 10517932